Are the Aging Male's Symptoms (AMS) scale and the Androgen Deficiency in the Aging Male (ADAM) questionnaire suitable for the screening of late-onset hypogonadism in aging Chinese men?. (17th July 2013) - Chen, Wei; Liu, Zhi-Yong; Wang, Lin-Hui; Zeng, Qin-Song; Wang, Hui-Qing; Sun, Ying-hao
Abstract: The Aging Male's Symptoms (AMS) scale and the Androgen Deficiency in the Aging Male (ADAM) questionnaire have been widely used for screening men suspected of late-onset hypogonadism (LOH). We evaluated the consistency of the two questionnaires with sex hormone levels. A total of 985 men completed the two questionnaires, as well as an analysis of the serum levels of total testosterone (TT), bioavailable testosterone (BT), luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol (E2), prolactin (PRL) and sex hormone-binding globulin (SHBG). No correlation was observed between any hormone level and the psychological or somatic section of the AMS score, whereas the sexual section was correlated with the levels of FT, LH, FSH, SHBG and BT. Significant correlations were observed between the result of the two questionnaires and these hormone levels. When LOH was defined as TT < 300 ng/dl and FT < 5 ng/dl, the sensitivity and specificity of the AMS scale were 54.0% and 41.2% compared with 78.7% and 14.8% for the ADAM questionnaire. Several sex hormone levels correlated with the two questionnaires, but neither of these questionnaires had sufficient sensitivity and specificity. It is necessary to provide a new questionnaire applicable to the Chinese population to screening LOH.